THE INFLUENCE OF BRAND IMAGES YAMAHA MIO MOTORCYCLE ON CV BURSA MOTOR YAMAHA, KABANJAHE - Ingan Ukur Br Sitepu; Chyty Emmyca Br Bangun (OISAA, 2020)
The image of the Yamaha Mio brand is one of the most important factors because the citramerk is very important to sell to prospective consumers, given the competition in the motorcycle business today can be categorized as a battle for the formation and maintenance of product images in the eyes of consumers. The purpose of this research in this thesis is to determine the extent of the influence of citramerk on YamahaMio's furniture decisions in CV. Kabanjahe Yamaha Motorcycle Exchange. This type of research is quantitative descriptive, data sources used are primary data and secondary data. Data collection techniques are through questionnaires, interviews and observations. The analytical method used is simple linear regression analysis method. The population in this study are consumers who have bought or used YamahaMio on CV. Kabanjahe Yamaha Motor Exchange, amounting to 290 people / month. The number of respondents to be sampled is 75 people. The results showed that the independent variables influenced furniture decisions. This is indicated by the results of partial testing of the calculated t value of the citramerk variable (X) of 11.284 greater than the t table of 1.982. Adjust R Square of 0.636 which means that the variable citramer has the ability to explain the YamahaMio purchase decision on the CV. The Kabanjahe Yamaha Motor Exchange was 63.6% while the remaining 46.4% was by other factors not examined in this study. The conclusion of this research is that citramerk influences the purchase decision of YamahaMio on CV. Kabanjahe Yamaha Motorcycle Exchange.